Psychology of male and female communicative activity - Vasyura, Svetlana A. (The Spanish Journal of Psychology, 2008)
The article features a brief overview of theoretical and empirical studies in communication psychology and sociability of men and women, boys and girls. Russian and foreign studies are summarized to point out that girls and women place greater emphasis on communication and interpersonal relations than do boys and men. Moreover, female communication is more emotional. The article presents the results of the author’s own empirical study of male and female communicative activity. Communicative activity is viewed as a complex psychological phenomenon, a degree of the subject’s willingness to interact. Communicative activity was studied with the test proposed by the Russian psychologist, Krupnov, and designed to detect the following components of communicative activity: dynamic (natural), emotional, motivational, cognitive, regulatory, productive, and two sorts of communication difficulties (operational and personal). Gender differences in communicative activity are shown on a sample of 480 participants aged 18-40 (240 men and 240 women). The article then describes communicative styles of adolescents (130 boys and 130 girls, aged 19-24). Various communicative styles are featured, including “energetic, businesslike,” “conformal, emotional,” “diplomatic, externally oriented” for boys and “energetic, sociable,” “emotional, difficult,” and “complaisant, expressive” for girls. Every person’s individuality and gender identity are shown to impact their communicative style.